Cyberloafing Behavior and Its Effects Towards Academic Achievement Among Students in Higher Education Institution - Tan Kim Mei; Ahmad Fahmi Mahamood; Shuhairimi Abdullah; Tengku Kastriafuddin Tengku Yakob; Zuraidi Ahmad Mokhdzar (Journal of Human Development and Communication (JoHDeC), 2025)
The objective of this study is to analyze the purposes of students in higher education institutions using a digital device for non-academic purposes. The researcher collected the research data from 370 undergraduate students studying at Universiti Malaysia Perlis using an online questionnaire that assessed with cyberloafing scale of Akbulut et al. (2016), which contain five dimensions of cyberloafing behavior: sharing, shopping, realtime updating, access to online content and gaming/ gambling. The relationship among the factor of gender towards the cyberloafing behavior and relationship between the cyberloafing behavior and academic achievement of undergraduate students have been tested by Pearson’s correlation test. Hypothesis Ha1 was rejected because there is no association between the gender factor and cyberloafing behavior. Hypothesis Ha2 was accepted because there is a significant relationship between cyberloafing behavior and academic achievement of undergraduate students. This study aids in adapting and validating the cyberloafing scale in the Malaysian environment under university students of the public sector, as most of the studies that applying cyberloafing behavior in the education setting are in Turkish which are not suitable to apply in the cultural context of Malaysia.